2019
DOI: 10.3389/fbuil.2019.00093
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Testing of a Small-Scale Truss Beam That Adapts to Loads Through Large Shape Changes

Abstract: Adaptive structures have the ability to modify their shape and internal forces through sensing and actuation in order to maintain optimal performance under changing actions. Previous studies have shown that substantial whole-life energy savings with respect to traditional passive designs can be achieved through well-conceived adaptive design strategies. The whole-life energy comprises an embodied part in the material and an operational part for structural adaptation. Structural adaptation through controlled la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…The formulation stated in Equations (39) and (40) has been extended to geometrically non-linear problems in [29]. Other formulations exist that include buckling constraints [17].…”
Section: Shape and Force Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The formulation stated in Equations (39) and (40) has been extended to geometrically non-linear problems in [29]. Other formulations exist that include buckling constraints [17].…”
Section: Shape and Force Controlmentioning
confidence: 99%
“…Numerical and experimental studies have shown that well-designed adaptive structures save up to 70% of the energy with respect to weight-optimized passive structures [14,15]. Recent studies [16,17] have investigated structural adaptation through large shape changes. In this case the structure is designed to be controlled into a shape that is optimal to counteract the effect of the external load.…”
Section: Introductionmentioning
confidence: 99%
“…Highrise structures, long-span bridges and self-supporting roof systems are generally stiffness governed and therefore they are could greatly benefit from adaptive design strategies. Structural adaptation through geometric non-linear control has been further investigated in Reksowardojo et al (2019Reksowardojo et al ( , 2020a. Numerical and experimental studies have shown that when the structure is designed to be controlled into shape configurations that are optimal to counteract the effect of the external load, the stress can be effectively homogenized and minimized under different loading conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The integration of such active elements allows an adaptive structure to monitor its stress state and to react accordingly. In case of rarely occurring, high external loads, the structure may induce forces counteracting those from the external load, respectively change its stiffness distribution to homogenize stresses and strains (Sobek and Teuffel, 2001;Senatore et al, 2018a), induce counter deformations (Sobek et al, 2002;Senatore et al, 2018b;Kelleter et al, 2020), or generate shape changes to establish a more efficient load transfer (Neuhaeuser et al, 2013;Reksowardojo et al, 2019), thus increasing structural performance. Due to this increase in performance, the passive elements of the adaptive structure can be dimensioned for lower, more frequently occurring loads, which reduces the structures' resource consumption and embodied energy while using comparatively little operational energy (Senatore et al, 2018c;Schlegl et al, 2019).…”
Section: Introductionmentioning
confidence: 99%